Performance Analysis of Multi-UAV Optical Communication Systems Over Foggy Channel Under Málaga Turbulence and Pointing Error Impairments - Guanjun Xu; Xiaozong Yu; Jialin Wang; Zhaohui Song; Qinyu Zhang (IEEE Photonics Journal)
Free-space optical (FSO) communication technology is widely utilized in uncrewed aerial vehicle (UAV) communication because it provides larger communication bandwidth than radio frequency technology. However, the system performance of FSO-based UAV communication systems is severely affected by several adverse factors, such as atmospheric turbulence, fog-induced absorption, and pointing errors, all of which result in performance deterioration drastically. This study proposes a multi-UAV optical communication system to suppress the influence of the foggy channel and pointing error impairments under atmospheric turbulence with a Málaga distribution, with both amplify-and-forward (AF) and decode-and-forward (DF) protocols, respectively. Specifically, some critical statistical expressions, such as probability and cumulative density functions, were derived, which were employed to assess the performance metrics, including outage probability, average bit error rate, and ergodic capacity. Additionally, these performance metrics obtained through theoretical analysis in the presence of atmospheric turbulence, fog absorption, and pointing errors were corroborated by Monte Carlo simulations. Finally, the performance indicators under AF and DF relay protocols were compared.